Integrated Four-Wavelength DFB Diode Laser Array for Continuous-Wave THz Generation - Mengdie Sun; Shaoyang Tan; Fei Guo; Songtao Liu; Qiang Kan; Dan Lu; Ruikang Zhang; Wu Zhao; Song Liang; Wei Wang; Ronald Broeke; Francisco. M. Soares; et al. (IEEE Photonics Journal)
We demonstrate a four-wavelength distributed feedback (DFB) diode laser array integrated with a semiconductor optical amplifier (SOA) for widely tunable terahertz (THz) mode-beating generation. The InP-based monolithically integrated chip consists of DFB laser diodes, an SOA, and a multimode interference (MMI) coupler. Microheaters and electrode plates are integrated on top of each DFB section for continuous and independent wavelength tuning. By heterodyning the output from the DFB lasers on a Uni-Traveling Carrier Photodiode (UTC-PD) integrated antenna, a continuous THz radiation ranging from 0.1 to 2.25 THz was obtained.